2020
DOI: 10.3390/pathogens9121062
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation as a Complex Result of Virulence and Adaptive Responses of Helicobacter pylori

Abstract: Helicobacter pylori is a bacterium that is capable of colonizing a host for many years, often for a lifetime. The survival in the gastric environment is enabled by the production of numerous virulence factors conditioning adhesion to the mucosa surface, acquisition of nutrients, and neutralization of the immune system activity. It is increasingly recognized, however, that the adaptive mechanisms of H. pylori in the stomach may also be linked to the ability of this pathogen to form biofilms. Initially, biofilms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 114 publications
2
46
0
Order By: Relevance
“…The downregulation effect of the combined use was greater than that of the single use. Many interactions have occurred during the formation of microbial biofilms, and it is difficult to clearly assess the usefulness or unavailability of H. pylori genes during the formation of this complex structure [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The downregulation effect of the combined use was greater than that of the single use. Many interactions have occurred during the formation of microbial biofilms, and it is difficult to clearly assess the usefulness or unavailability of H. pylori genes during the formation of this complex structure [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Biofilms play a vital role in resisting external threats, and H. pylori has the ability to form biofilms in vivo and in vitro [ 11 , 12 ]. The matrix of H. pylori biofilms contains mannan and LPS-related structures, extracellular DNA (eDNA), protein, and outer membrane vesicles (OMV) [ 13 ]. Studies have shown that H. pylori biofilms increase clarithromycin, amoxicillin, and metronidazole resistance in vitro, and the expression of proton pump genes related to antibiotics is increased 10–1000 times compared with the planktonic state [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the first cluster of alkyloxy derivatives (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), the MIC results demonstrated no or weak efficacy against all the strains as well as their parent compound, despite the presence of branched alkyl chains, unsaturations or specific functional groups (ketone, carboxylic acid, ethyl ester). Only three derivatives (3,9,12) with linear and increasing alkyl chains (Et, n-Pr, n-Bu) presented improved MIC values with respect to thymol against some clinical isolates (MIC/MBC = 16 µg/mL).…”
Section: Anti-helicobacter Pylori Activity and Structure-activity Relmentioning
confidence: 99%
“…The survival of the microorganism as well as the recalcitrance of the infection are due to H. pylori aptitude to adapt itself to the host and to develop resistance towards the antimicrobials commonly used in therapy [5]. The resistance rate to the clinically approved drugs is increasing worldwide and most of the therapeutic failures are ascribed to adaptive mechanisms linked to the biofilm formation [6], which limit the efficacy of the current therapy. The triple therapy based on the administration on proto-pump inhibitor and two antibiotics has been considered the standard therapy for many years, however, the increasing rate of triple-therapy failure was registered in many countries as well as the spreading of H. pylori antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori presents a lipopolysaccharide (LPS), virulence factors, and even the capacity of forming a biofilm, which helps in neutralizing immune response. Biofilm formation has been attributed to morphological changes (cell wall rearrangement), membrane vesicles secretion, and inter-microbial communication, which constitute virulence and adaptive responses of the pathogen [6,7]. Eradication of the infection is therefore essential for Int.…”
Section: Introductionmentioning
confidence: 99%